Mechanism of Qingjie Fuzheng Granules on alleviating 5-FU chemotherapy-induced intestinal mucositis in a mouse model of Colorectal Cancer by regulating Cathepsin B/NLRP3 pathway - Yuan Yingfei; Lin Jiumao; Lin Minghe; Zhao Jinyan; Chen Xuzheng; Liu Jinhong; Zhu Xiaoqin (康复学报)
ObjectiveTo investigate the therapeutic effect and mechanism of Qingjie Fuzheng Granules on 5-FU chemotherapy-induced intestinal mucositis in a mouse model of Colorectal Cancer based on Cathepsin B/NLRP3 pathway.MethodsTwenty-four male BALB/c mice were inoculated with CT26 cells subcutaneously in the axillary of the right forelimb to construct a mouse model of colorectal cancer subcutaneous xenograft. When the tumor size reached 100-300 mm3, the mice were randomly divided into the control group, 5-FU group and 5-FU+ Qingjie Fuzheng Granules group (5-FU+QFG), 8 mice in each group. The mice in the control group were given normal saline by gavage and intraperitoneal injection, while those in each other group were given intraperitoneal injection of 5-FU (50 mg/kg d-1) once daily for five successive days. The 5-FU+QFG group was given Qingjie Fuzheng Granules (1.0 g/kg d-1) by gavage at the same time of chemotherapy, once a day, for seven successive days. The diarrhea of the mice was observed every day for seven days, and the body weight and tumor volume were measured and recorded. After the last administration of the drug on the seventh day, the mice were fasted for 12 h, then, animal samples of mice were collected for experimental detection. The pathological morphology of jejunum tissue was observed by HE staining. The expressions of diamine oxidase (DAO), D-lactic acid (D-LA), endotoxin (ET), tumor necrosis factor-α(TNF-α), interleukin -1β(IL-1β) and interleukin -6(IL-6) in serum were detected by ELISA. The positive expression of Cathepsin B in the jejunum tissue was detected by immunohistochemistry. The mRNA expression levels of ZO-1 and Occludin in the jejunum tissue were detected by real-time quantitative PCR, and the protein expressions of ZO-1, Occludin, Cathepsin B, NLRP3, ASC and cleaved Caspase-1 in the jejunum tissue were detected by Western blot.ResultsDuring the experimental period, Qingjie Fuzheng Granules significantly alleviated the diarrhea symptoms induced by 5-FU (P<0.05), but did not significantly improve the body weight loss induced by 5-FU (P>0.05). There was no significant synergistic effect of 5-FU on the inhibition of tumor growth (P>0.05). QFG could significantly improve the symptoms of intestinal mucosal injury caused by 5-FU, such as shortened villi, deeper crypts, and infiltration of inflammatory cells. Compared with the 5-FU group, QFG significantly reduced the expressions of DAO, D-LA and ET as well as pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 in mouse serum (P<0.05); The protein expression of Cathepsin B in jejunum tissue of 5-FU+QFG group was significantly reduced(P<0.05), The protein expression levels of NLRP3, ASC, cleaved Caspase-1 in the jejunum tissue of 5-FU+QFG group were decreased (P<0.05). The mRNA and protein expression levels of tight junction proteins ZO-1 and Occludin in jejunum tissue of 5-FU+QFG group were increased (P<0.05);ConclusionQingjie Fuzheng Granules can reduce the release of pro-inflammatory factors, inhibit the intestinal mucosal inflammatory response and repair the intestinal mucosal barrier damage by regulating the Cathepsin B/NLRP3 pathway, thereby alleviating the chemotherapy-induced intestinal mucositis induced by 5-FU.